(untitled) (Shanti Journal, 2024)
The rights of crime victims are an important consideration in the criminal justice system. In Nepal, there are a number of prevailing laws that outline the rights and protections afforded to victims of crime. This study provides an overview of the key rights and entitlements of crime victims under Nepalese law.The prevailing laws of Nepal recognize the need to protect and support victims of crime throughout the criminal justice process. Under the Criminal Procedure Code of Nepal, victims have the right to be informed about the progress of the case, to participate in the proceedings, and to receive compensation for losses incurred as a result of the crime. The Domestic Violence (Offense and Punishment) Act further safeguards the rights of victims of domestic violence, granting them the ability to seek protection orders and access emergency support services. Additionally, the National Criminal Justice Coordination Committee has established a Victim Support Fund to provide financial assistance and rehabilitation services to victims. This fund can cover expenses such as medical bills, legal fees, and livelihood support. Victims also have the right to confidentiality and privacy, and measures are in place to protect them from intimidation or retaliation.While Nepal’s laws demonstrate a commitment to upholding victim rights, challenges remain in terms of effective implementation and access to support, especially for marginalized groups. Ongoing efforts are needed to strengthen the capacity of the criminal justice system to consistently fulfill its obligations to crime victims. Overall, the legal framework in Nepal represents an important foundation for ensuring victims are treated with dignity, provided with necessary resources, and empowered to participate in the justice process.